PENGEMBANGAN MODUL PRAKTIKUM UNTUK PERBANDINGAN UNJUK KERJA LINE CODING RZ DAN NRZ PADA JARINGAN FIBER OPTIK - I Putu Aldha Rasjman Sayoga; Pande Ketut Sudiarta; Nyoman Putra Sastra (Program Studi Teknik Elektro UNUD, 2021)
The important thing to consider in the process of sending optical fiber network signals is theselection of line coding types. Line coding is a process of converting digital data into digital signals sothat they can be transmitted in optical fiber networks. Line codings commonly used are NRZ and RZ.Therefore, this research discussed the comparison of the performance of NRZ and RZ line codings infiber-optic networks in terms of Q-Factor, BER, and Eye Diagram. The result of this research was thecharacteristic form of the electric signal line coding NRZ with one data element using one signalelement, while in the RZ coding line, one data element used two signal elements. The maximum risetime variable using the RZ coding line is 0.3 bits, while the NRZ coding line is 0.7 bits. The bestrectangle shape model using line coding RZ is sine while line coding NRZ is exponential. Themaximum bit rate using the RZ coding line is 11.5 Gbps while using the NRZ coding line is 18 Gbps.The maximum transmission distance using the RZ and NRZ coding line is 75 km. Another output ofthis research is a practicum module that can be used by students of the Electrical Engineering StudyProgram to understand optical communication systems, especially line coding RZ and NRZ. Based onthe results of student assessments of 87.6% and the post-test score which is higher than the pre-testscore, the practicum module is feasible as teaching material.